A Randomized Controlled Trial to Increase Cancer Screening and Reduce Depression Among Low-Income Women. Issue 3 (August 2022) - Tobin, Jonathan N.; Weiss, Elisa S.; Cassells, Andrea; Lin, TJ; Holder, Tameir; Carrozzi, Gianni; Barsanti, Franco; Morales, Alejandra; Mailing, Alison; Espejo, Maria; Gilbert, Erica; Casiano, Louann; et al.
Low-income women of color receive fewer cancer screenings and have higher rates of depression, which can interfere with cancer screening participation. This study assessed the comparative effectiveness of two interventions for improving colorectal, breast, and cervical cancer screening participation and reducing depression among underserved women in Bronx, NY, with depression. This comparative effectiveness randomized controlled trial (RCT) with assessments at study entry, 6, and 12 months utilized an intent-to-treat statistical approach. Eligible women were aged 50 to 64, screened positive for depression, and were overdue for ≥ 1 cancer screening (colorectal, breast, and/or cervical). Participants were randomized to a collaborative depression care plus cancer screening intervention (CCI + PCM) or cancer screening intervention alone (PCM). Interventions were telephone-based, available in English or Spanish, delivered over 12 months, and facilitated by a skilled care manager. Cancer screening data were extracted from electronic health records. Depression was measured with a validated self-report instrument (PHQ-9). Seven hundred fifty seven women consented and were randomized (CCI + PCM, n = 378; PCM, n = 379). Analyses revealed statistically significant increases in up-to-date status for all three cancer screenings; depression improved in both intervention groups. There were no statistically significant differences between the interventions in improving cancer screening rates or reducing depression. CCI and PCM both improved breast, cervical, and colorectal cancer screening and depression in clinical settings in underserved communities; however, neither intervention showed an advantage in outcomes. Decisions about which approach to implement may depend on the nature of the practice and alignment of the interventions with other ongoing priorities and resources.